“Smart support for fruit farm business decision-making: A framework for digital controlling adoption” - Luis Müller; Robert Luer; Wolfgang Lentz (Smart Agricultural Technology)
Decision-makers in horticultural enterprises face significant challenges, including structural changes toward fewer and larger enterprises, increasing weather extremes, skilled labor shortages, and increasing sustainability demands. Addressing these challenges requires the use of effective business management instruments. However, initial research suggests that controlling is practiced infrequently and with limited intensity in the sector. This study investigates barriers to and drivers of the adoption of controlling, focusing on the role of digital transformation in enhancing its use. Nineteen semi-structured interviews and farm inspections were conducted with 28 current and prospective farm managers in the fruit-growing sector in Germany and Luxembourg. Results show that decision-making is primarily driven by experience and intuition. Lack of experience with controlling hinders the visibility of its benefits, thus preventing the acquisition of controlling expertise. In the absence of such expertise, controlling methods cannot be effectively implemented, rendering the benefits elusive. Additionally, the limited availability of processed data restricts meaningful business analyses. Farm management and information systems (FMISs) provide minimal controlling functionalities. Reporting obligations relating to crop protection are the primary drivers for FMIS adoption. Therefore, reporting obligations in external accounting and data requirements for funding and loan procurement serve as entry points for controlling-focused software solutions. Information and controlling systems thus hold potential to enhance routine decision-making, rendering the benefits of controlling more tangible. This study contributes a conceptual framework to broaden the understanding of the often negatively perceived cost-benefit ratio of controlling in small and medium-sized enterprises and identifies strategies to strengthen its practical relevance.